2002
DOI: 10.1002/pros.10109
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a plasma membrane Ca2+‐ATPase in epithelial cells and aposomes of the rat coagulating gland

Abstract: We show for the first time that Ca(2+)-ATPase as an important, functionally active membrane protein of the apical plasma membrane is incorporated into the aposomal membranes and is released from the cells during apocrine secretion process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…5A). The expression of murine PMCA4a in the apical plasma membranes of the epididymis strongly suggests that it is secreted into the lumen: PMCA concentrated in glandular epithelial cells in a variety of tissues is known to be secreted (e.g., into milk from the apical membrane of lactating mammary gland epithelia) [34][35][36][37]. Indeed, Western blots revealed that the ELF from each epididymal region contained the ;128-kDa PMCA4a variant (Fig.…”
Section: Pmca4 Splice Variants Are Differentially Expressed In Testismentioning
confidence: 93%
“…5A). The expression of murine PMCA4a in the apical plasma membranes of the epididymis strongly suggests that it is secreted into the lumen: PMCA concentrated in glandular epithelial cells in a variety of tissues is known to be secreted (e.g., into milk from the apical membrane of lactating mammary gland epithelia) [34][35][36][37]. Indeed, Western blots revealed that the ELF from each epididymal region contained the ;128-kDa PMCA4a variant (Fig.…”
Section: Pmca4 Splice Variants Are Differentially Expressed In Testismentioning
confidence: 93%
“…The exact function of the cells with a "knobbled" apical surface, also referred to as blebs or cells with pitted surfaces (Motta and Andrews, 1976;Post et al, 2002), is unknown, although they may also be associated with apocrine secretions (Girling, 2002). Aposomes, which are the apical protrusions of the plasma membrane prior to apocrine secretion, are initially derived from apical microvilli (Post et al, 2002).…”
Section: Morphological Attributes Suggesting Histotrophic Nutrient Trmentioning
confidence: 99%
“…Aposomes, which are the apical protrusions of the plasma membrane prior to apocrine secretion, are initially derived from apical microvilli (Post et al, 2002). After an apical portion of the cell pinches off from the plasma membrane, the remaining part of the cell repairs itself and repeats the secretory process (Tortora and Grabowski, 1996).…”
Section: Morphological Attributes Suggesting Histotrophic Nutrient Trmentioning
confidence: 99%
“…in the intestines and distal tubules of the kidney (Friedman and Gesek 1995;Hoenderop et al 2002;Larsson and Nemere 2002). In secretory epithelial cells such as pancreatic acinar cells, salivary gland cells and in epithelial cells of the rat-coagulating gland, PMCA is largely concentrated in the apical plasma membrane (Belan et al 1996; Lee et al 1997;Post et al 2002). The principal cells of the epididymis combine both resorptive and secretory functions (Cooper 1999), therefore, the localization of PMCA in the plasma membrane in the caput epididymidis is conclusive; it indicates that PMCA4 contributes substantially to vectorial, transcellular Ca 2+ transport from the apical to the basolateral compartment.…”
Section: Distribution Of Pmca4 In Rat Epididymismentioning
confidence: 99%